Alkaline developing solution composition for solar cell copper interconnection process and preparation method and application of alkaline developing solution composition

By regulating the content of each component in the developer composition, the problem of insufficient developer in the copper interconnection process of solar cell cells is solved, fast development, cleanness, good wettability, no foaming, and reduced PVD copper The corrosion rate is suitable for the graphical development process of thin line width of the copper process of solar cell.

CN119493345APending Publication Date: 2025-02-21SUZHOU HAOSHEN INTELLIGENT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620896.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Prior Art In the copper interconnection process of solar cell cells, alkaline developer is difficult to achieve rapid development, cleanness, good wetting, no foaming, and high corrosion rate for PVD copper.

Method used

By regulating the content of each component in the developer composition, including inorganic alkaline substances, buffers, copper preservatives, surfactants and defoamers, synergistically, a specific type of copper preservatives and defoamers are added, and the specific types of copper preservatives and defoamers are used. A patterned development process for copper interconnection of heterojunction or other types of solar cell cells.

Benefits of technology

It achieves fast development, clean development, good wetting properties of the developer, no bubbles, and low corrosion rate on the substrate PVD copper, which is suitable for the pattern development process of thin line width of the copper process of solar cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133414190000091
    Figure BDA0005133414190000091
Patent Text Reader

Abstract

The invention discloses an alkaline developing solution composition for a solar cell copper interconnection process as well as a preparation method and application of the alkaline developing solution composition, and the alkaline developing solution composition comprises the following components in percentage by mass: 0.8-1.2% of an inorganic alkaline substance, 0.1-0.5% of an inorganic substance buffering agent, 300-1000 ppm of a copper preservative, 500-1500 ppm of a surfactant, 500-1200 ppm of a defoaming agent and the balance of pure water. According to the alkaline developing solution, the content of each component in the developing solution composition is regulated and controlled, each component has a synergistic effect, and specific types of copper preservatives and defoaming agents are added, so that the alkaline developing solution is used for a graphical developing process for copper interconnection of heterojunction or other types of solar cells, is suitable for developing positive photoresist, and has a wide application prospect. The method has the characteristics of high developing speed, high developing cleanness, high developing solution wettability, no blistering, low substrate PVD (Physical Vapor Deposition) copper corrosion rate and the like, and is beneficial to the realization of a thin-line-width graphical developing procedure in the copper manufacturing process of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of developer solutions, and in particular to an alkaline developer solution composition for a solar cell copper interconnection process, and a preparation method and application thereof. Background Art

[0002] Conductive silver paste, which is a mixture of metallic silver powder and a binding phase such as organic polymer or glass powder, is required in the production process of traditional solar cells. Silver is widely used in both crystalline silicon solar cells and thin-film solar cells. In crystalline silicon solar cells, silver is mainly used to make electrodes on the front and back. The conductive silver paste is printed on the silicon wafer through processes such as screen printing, and then sintered to form electrodes. In thin-film solar cells, silver is also often used to make electrodes and conductive lines to connect various functional areas. The high conductivity and good chemical stability of silver enable it to effectively collect and transmit current, and maintain the performance of the electrode during long-term use. At the same time, the silver electrode has good adhesion to the silicon wafer or other thin film materials, which can ensure the stability of the battery under various environmental conditions.

[0003] Improving photoelectric conversion efficiency and reducing production and manufacturing costs are the two major driving forces for the market application of solar energy. From the cost analysis of solar cells, silver paste is the second highest proportion of raw materials after silicon wafers. Silver is a precious metal, expensive and scarce. In the production of solar cells, the cost of silver accounts for a high proportion, especially in large-scale production. The cost of silver will have a greater impact on the total cost of solar cells. As the output of solar energy increases year by year, the price of silver will continue to rise, and other cheap metals need to be found urgently. Compared with silver, copper is a common metal with much larger reserves and mining volume than silver, and its price is much lower than silver. The unit weight price of copper is only about one percent of that of silver. From a cost perspective, using copper instead of silver in solar cells will greatly reduce production costs if some performance defects of copper can be overcome.

[0004] The new heterojunction solar cell has high photoelectric conversion efficiency and is favored by the market, but the amount of silver paste used is higher, and it is more urgent to use copper to replace silver as the metallization electrode. Here, the copper interconnection process of heterojunction solar cells is used as an example, which can also be used for other types of solar cell copper interconnection processes. The use of electroplating copper process to fully replace the existing silver process can greatly reduce the production and manufacturing cost of heterojunction solar cells. The main production process is: physical vapor deposition (PVD) to produce a copper seed layer on the surface of the cell, patterning of the mask layer, electroplating of copper / nickel / tin, and removal of the mask layer. The specific plan is that in the patterning process of the heterojunction copper process, a very thin copper seed layer with a thickness of about 0.1 microns is first sputtered on the surface of the transparent conductive film (TCO) of the silicon wafer by physical vapor deposition (PVD). Then, a mask material (photosensitive ink, photoresist, etc.) is used to make a mask layer by a wet film method. The mask material is evenly coated on the copper seed layer. After coating and drying, a special patterned mask is used as a mask for UV exposure or laser direct writing for maskless exposure. After exposure by the exposure machine, the pattern on the mask layer will undergo chemical or physical changes. The mask layer in the exposed area is removed by the developer, while the photoresist in the unexposed area is retained to form the required pattern. These patterns will serve as templates for subsequent copper electroplating, determining the shape and position of the copper grid line. Since there are two types of photosensitive materials used as masks, one is ink-based negative photoresist and the other is phenolic-based positive photoresist. The line width of ink-based negative photoresist is large and cannot achieve a line width of 10um or even 5um in the future, so more and more manufacturers of copper electroplating processes are beginning to try using positive photoresist. Although positive photoresist has the characteristics of high resolution and easy degumming, the coating film thickness required for the cell is more than 10um, and the patterning resolution is 8um. The traditional 2.38% TMAH (tetramethylammonium hydroxide) has weak penetration ability and insufficient wettability from the top of the photoresist to the bottom of the pattern, which has a great impact on the pattern, resulting in a low patterning angle (70-75°). In addition, since the photoresist contains special additives, it is easy to bubble during development, covering the surface of the cell, preventing the developer from continuing to develop, and affecting subsequent rinsing. In addition, PVD copper has insufficient bonding strength and is easily corroded in alkaline developers. Traditional alkaline developers on the market can easily corrode the copper surface, which will affect subsequent processes.

[0005] Based on this, there is an urgent need for a new alkaline developing composition that has the characteristics of fast development, clean development, and good wettability when developing positive photoresists, while also having no bubbling during development and the lowest corrosion rate for the substrate copper, so as to meet the graphical development requirements of fine-line copper interconnects of solar cells with a width of less than 10 microns. Summary of the invention

[0006] The present invention aims at the deficiencies in the prior art and provides an alkaline developer composition for a solar cell copper interconnection process and a preparation method and application thereof. The content of each component in the developer composition is regulated, the components act synergistically, and specific types of copper preservatives and defoamers are added. The alkaline developer is used in a graphic development process of heterojunction or other types of solar cell copper interconnections, is suitable for the development of positive photoresists, has the characteristics of fast development, clean development, good developer wettability, no bubbling, low corrosion rate of substrate PVD copper, etc., and is conducive to realizing a graphic development process of fine line width in a solar cell copper process.

[0007] In order to solve the above technical problems, the present invention provides an alkaline developer composition for the copper interconnection process of solar cells, which comprises the following components by mass percentage: 0.8-1.2% of an inorganic alkaline substance, 0.1-0.5% of an inorganic buffer, 300-1000ppm of a copper preservative, 500-1500ppm of a surfactant, 500-1200ppm of a defoaming agent, and the rest is pure water.

[0008] The present invention controls the content of inorganic alkali between 0.8% and 1.2%. If the content is lower than 0.8%, the corresponding dissolution rate becomes slower, which is easy to cause development residue. At this time, the UV exposure of the photoresist needs to be increased, but at the same time, the production rhythm of the exposure process is affected; if the content is too high, greater than 1.2%, it is easy to over-develop during development, affecting the development size, and further affecting the size of the subsequent electroplated copper.

[0009] In the process of developing, the inorganic developer reacts with carbon dioxide in the air, slowly reducing the alkali concentration, which can easily cause insufficient subsequent developing ability. In order to maintain the ability of the developer, the present invention adds a certain amount of buffer to the alkaline developer, which can generate hydroxide ions when ionized, thereby continuing to maintain the concentration and developing ability of the developer. When the amount of the buffer added is less than 0.1%, the ability to provide hydroxide ions is insufficient and does not help improve the developing ability. However, when the amount added is greater than 0.5%, it affects the main alkali content, which greatly improves the developing ability, affects the developing resolution and side wall angle, and has an adverse effect.

[0010] The surface tension of the inorganic alkali developer is greater than that of the organic alkali, so that the developer does not have sufficient wettability when developing the seepage groove or deep hole pattern, and cannot penetrate into the bottom of the pattern, which easily causes the phenomenon that the pattern is larger on the top and smaller on the bottom during development. The present invention adds a special surfactant to the developer to reduce the surface tension of the inorganic alkali developer, improve the wettability of the developer to deep grooves and deep holes, and improve the angle of the pattern. The thickness of the coated photoresist film of the heterojunction pattern is between 10-15um, and the resolution of the pattern is above 5um, and the main aspect ratio reaches 1:2 or 1:3. With the development of technology, the resolution can be higher and higher, and the requirements for the developer will also be higher and higher. The amount of surfactant added needs to be controlled within a certain range. If the content is lower than 500ppm, the ability to reduce the surface tension is insufficient. If it is higher than 1000ppm, the wettability is too large, which easily causes bottom erosion during development, forming undercut.

[0011] In chain developer development, with the increase of developer spray pressure and linear speed, bubbles are easily generated during development. The main reason is that in order to improve the uniformity of coating film thickness, a surfactant is usually added to the photoresist. During alkaline development, the surfactant is dissolved into the developer. Since the developer is an aqueous system and the photoresist is an oily system, bubbles are generated. The present invention adds a special system of defoamer to the developer system to suppress or defoam. The defoamer content has a certain control range. If it is lower than 500ppm, the defoaming ability is insufficient. If it is higher than 1200ppm, although the defoaming ability is effectively improved, it will cause the photoresist surface to bloom, which may have an adverse effect on the subsequent electroplating process.

[0012] In a heterojunction structure, the photoresist-coated substrate is 5-10um PVD copper. Increasing the developer concentration or the developer temperature will cause corrosion to the PVD copper. The present invention adds a certain amount of copper preservative to the alkaline developer system to form a protective layer on the copper surface during development, thereby protecting the copper. The copper preservative has certain requirements for content. If the content is less than 300ppm, the bottom copper material cannot be effectively and comprehensively protected. If the content is greater than 1000ppm, the bottom copper is overprotected, which will reduce the developing effect of the developer and the developing rate of the developer, thereby causing the problem of difficulty in removing the glue.

[0013] Further, the copper preservative is selected from one or more of methylbenzotriazole, 2,5-dimercapto-1,3,4-thiadiazole, hydroxybenzothiazole, 3-mercapto-1,2-propylene glycol, 2-thioglycerol, aminotrimethylphosphonic acid, dithiodiethanol, glycerol, 1,3,5-triazine-2,4,5-trithiol, 2-mercapto-6-hydroxybenzothiazole, and 6-anilino-1,3,5-triazine-2,4-dithiol. Preferably, it is selected from 1,3,5-triazine-2,4,5-trithiol and / or 6-anilino-1,3,5-triazine-2,4-dithiol.

[0014] The present invention targets the PVD copper layer and selects a specific copper preservative. The triazine thiol molecular structure contains a thiol group (-SH). When in contact with copper, the thiol group can react chemically with copper. Sulfur atoms have a strong affinity for copper and interact with metal atoms on the copper surface to form a tight protective film of sulfur-containing compounds. This protective film can effectively block direct contact between oxygen, moisture, corrosive ions such as -OH in the external environment and the copper surface, thereby slowing down the corrosion process of copper. The formed protective film has high stability and is not easily destroyed. On the one hand, there is a certain intermolecular force between the triazine thiol molecules, so that the protective film has good structural integrity; on the other hand, the protective film has a strong bonding force with the copper surface and can be firmly attached to the copper surface. It can not only cover the copper surface during static development, but also provide good protection under the kilogram-level pressure impact of the chain developer.

[0015] Furthermore, the defoaming agent is selected from one or more of non-silicone polyether higher alcohols and polysiloxanes, for example: TEGO Foamex 810.

[0016] Polyether and siloxane copolymer molecules contain both hydrophilic polyether segments and hydrophobic siloxane segments. Among them, the siloxane segments have low surface energy and can quickly migrate to the surface of the liquid to reduce the surface tension of the liquid; when the surface tension is reduced to a certain extent, the stability of the foam film is destroyed, resulting in foam bursting. The presence of polyether segments can increase the solubility and dispersibility of the copolymer in the aqueous phase, so that the copolymer can better play the role of reducing surface tension.

[0017] In addition, polyether and siloxane copolymers can be adsorbed on the gas-liquid interface to prevent new foam from forming. The adsorption of copolymer molecules on the gas-liquid interface can reduce the concentration of surfactant molecules on the interface and reduce the wrapping effect of surfactant molecules on the gas, thereby inhibiting the generation of foam.

[0018] Furthermore, the inorganic alkaline substance is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonia water.

[0019] Furthermore, the buffer is selected from one or more of sodium carbonate, sodium bicarbonate, disodium hydrogen phosphate, sodium hydrogen phosphate, sodium oxalate, sodium borate, ammonia water, and sodium borate.

[0020] Furthermore, the surfactant is selected from one or more of nonionic fatty acids, polyether-modified heptamethyltrisiloxane, polyether-modified silicone oil, and ether-modified polydimethylsiloxane copolymers, for example: MOK-2020.

[0021] Furthermore, the electrical conductivity of the pure water is 18.2 megohm-cm.

[0022] The second aspect of the present invention provides a method for preparing the alkaline developer composition according to the first aspect, comprising the following steps:

[0023] S1, mixing and dissolving pure water and an inorganic alkaline substance to obtain a mixed solution, and cooling the mixture to room temperature;

[0024] S2. Adding an inorganic buffer, a copper preservative, a surfactant, and a defoaming agent to the mixed solution at room temperature, mixing and dissolving, and filtering to obtain an alkaline developer composition.

[0025] Furthermore, the mixed dissolution conditions are: rotation speed 100-300 rpm, time 0.5-2h.

[0026] The third aspect of the present invention provides the use of the alkaline developer composition described in the first aspect in a development process for a patterned mask layer of a solar cell.

[0027] Beneficial effects of the present invention:

[0028] The present invention regulates the content of each component in the developer composition, the components act synergistically, and specific types of copper preservatives and defoamers are added. The alkaline developer is used in the graphic development process of copper interconnection of heterojunction or other types of solar cells, is suitable for the development of positive photoresists, has the characteristics of fast development, clean development, good developer wettability, no bubbling, low corrosion rate of substrate PVD copper, etc., and is conducive to realizing the graphic development process of fine line width of solar cell copper process. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present embodiment provides an alkaline developer composition for the copper interconnection process of solar cells, which comprises the following components by mass percentage: 0.8-1.2% of an inorganic alkaline substance, 0.1-0.5% of an inorganic buffer, 300-1000ppm of a copper preservative, 500-1500ppm of a surfactant, 500-1200ppm of a defoaming agent, and the rest is pure water, wherein the conductivity of the pure water is 18.2 megohm-cm.

[0031] As a preferred embodiment, the copper preservative is selected from one or more of methylbenzotriazole, 2,5-dimercapto-1,3,4-thiadiazole, hydroxybenzothiazole, 3-mercapto-1,2-propylene glycol, 2-thioglycerol, aminotri(methylenephosphonic acid), dithiodiethanol, glycerol, 1,3,5-triazine-2,4,5-trithiol, 2-mercapto-6-hydroxybenzothiazole, and 6-anilino-1,3,5-triazine-2,4-dithiol. Preferably, it is selected from 1,3,5-triazine-2,4,5-trithiol and / or 6-anilino-1,3,5-triazine-2,4-dithiol.

[0032] As a preferred embodiment, the defoaming agent is selected from one or more of non-silicone polyether higher alcohols and polysiloxanes, for example: TEGO Foamex 810.

[0033] As a preferred embodiment, the inorganic alkaline substance is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonia water.

[0034] As a preferred embodiment, the buffer is selected from one or more of sodium carbonate, sodium bicarbonate, disodium hydrogen phosphate, sodium hydrogen phosphate, sodium oxalate, sodium borate, ammonia water, and sodium borate.

[0035] As a preferred embodiment, the surfactant is selected from one or more of nonionic fatty acids, polyether-modified heptamethyltrisiloxane, polyether-modified silicone oil, and ether-modified polydimethylsiloxane copolymers, for example: MOK-2020.

[0036] Another embodiment provides a method for preparing the alkaline developer composition of the above embodiment, comprising the following steps:

[0037] S1, mixing and dissolving pure water and an inorganic alkaline substance to obtain a mixed solution, and cooling the mixture to room temperature;

[0038] S2. Add an inorganic buffer, a copper preservative, a surfactant, and a defoaming agent to the mixed solution at room temperature, mix and dissolve them at a rotation speed of 100-300 rpm for 0.5-2 h, and filter to obtain an alkaline developer composition.

[0039] Another embodiment provides the use of the alkaline developer composition described in the above embodiment in a development process of a patterned mask layer of a solar cell.

[0040] The following are specific embodiments.

[0041] Example 1

[0042] This embodiment provides a method for preparing an alkaline developer composition for a solar cell copper interconnection process, the preparation method comprising the following steps:

[0043] 18.2 megohm-cm pure water, sodium hydroxide, sodium borate, 6-anilino-1,3,5-triazine-2,4-dithiol, MOK-2020, and TEGO Foamex 810 were weighed according to masses of 986.7 kg, 10 kg, 2 kg, 0.5 kg, 0.8 kg, and 0.8 kg, respectively.

[0044] First, pure water and sodium hydroxide solid are stirred and dissolved in a 2000L Teflon-lined reaction tank. Heat will be released and the temperature will rise. After complete dissolution, the temperature is cooled to room temperature. Then sodium borate, 6-anilino-1,3,5-triazine-2,4-dithiol, MOK-2020, and TEGO Foamex 810 are added at a speed of 150rpm. Stir at room temperature for 0.5 hours. After no insoluble matter is observed with the naked eye, filter once with a 0.5um PFTE filter element (to eliminate insoluble matter) to obtain a developer composition.

[0045] The difference between Examples 2-4 and Comparative Examples 1-5 and Example 1 is the component formula of the developer composition, which is specifically shown in Table 1, wherein the copper preservative used in Comparative Example 5 is a commercially available preservative (polyol preservative), and the copper preservative used in other Examples and Comparative Examples is 6-anilino-1,3,5-triazine-2,4-dithiol; the defoamer used in Comparative Example 6 is a commercially available defoamer (organic silicon system), and the defoamer used in other Examples and Comparative Examples is Foamex 810. The other parameters and steps of the Examples and Comparative Examples are the same.

[0046] Table 1

[0047]

[0048] Application and performance testing

[0049] Patterned preparation: soak the PVD copper sheet in isopropanol for 5 minutes, blow dry with nitrogen, put it in a 100℃ oven, bake it for 5 minutes, cool it to room temperature, apply positive photoresist on the PVD copper sheet, bake it at 110℃ for 3 minutes, test the film thickness to 10±0.5um, and control the uniformity within 5%. Then put the copper sheet coated with photoresist under the exposure machine and expose it with a mask pattern with a line width of 8μm, and the exposure energy is 100mj / cm 2.

[0050] The alkaline developer composition prepared in the above-mentioned embodiment and comparative example is used in the development process after the photoresist is exposed, and the specific operation is as follows:

[0051] The developer prepared in the above-mentioned embodiments and comparative examples was poured into a chain developer, and the heating temperature was controlled at 23±1°C, and circulated for 1 hour. The patterned photoresist sheets were placed in the chain developer for development, and then rinsed with pure water and dried with nitrogen. The development results of the developer compositions of the embodiments and comparative examples were examined based on the following factors:

[0052] (1) The bubble height of the chain developer is controlled at 12 mm.

[0053] (2) Use a four-corner probe to test the reduction of PVD copper after development, with the target being less than 0.3um;

[0054] (3) The clean layer of the developed pattern, the target is developed cleanly, and there is no photoresist residue;

[0055] (4) Measurement of graphic angle after development, target > 80°.

[0056] The test results are shown in Table 2.

[0057] Table 2

[0058] category Development degree Graphic Angle Bubble height Copper reduction Comprehensive Assessment Target Clean without residue >80° <12mm <0.3um OK Example 1 Clean without residue 82.2° 6mm 0.18um OK Example 2 Clean without residue 81.3° 3mm 0.15um OK Example 3 Clean without residue 85.3° 3mm 0.09um OK Example 4 Clean without residue 81.8° 10mm 0.24 OK Comparative Example 1 Photoresist residue 82.1° 8mm 0.16um NG Comparative Example 2 Clean without residue 83.5° 6mm 0.45um NG Comparative Example 3 Clean without residue 84.2° 24mm 0.16um NG Comparative Example 4 Clean without residue 74.6° 9mm 0.2um NG Comparative Example 5 Clean without residue 82.4° 10mm 0.40 NG Comparative Example 6 Clean without residue 81.9° 19mm 0.24 NG

[0059] As shown in Table 2, the developers prepared in Examples 1-4 meet the product design expectations in terms of the four indicators of development degree, pattern angle, bubble height, and copper reduction, and will not affect the subsequent processes. The developer provided by the present invention is not only suitable for the solar cell patterning process, but also conducive to achieving the improvement of the fine line width development angle, which is more beneficial to the subsequent copper electroplating process.

[0060] However, the developer prepared in Comparative Examples 1-6 has a poor development effect and cannot meet the requirements. Among them, in Comparative Example 1, due to the low sodium hydroxide content, the exposed photoresist cannot be effectively dissolved during development, resulting in the inability to develop cleanly; the content of copper preservative in Comparative Example 2 is too low, resulting in the inability to effectively suppress the corrosion of sodium hydroxide to the copper metal of the substrate during development, and the corrosion amount becomes larger, exceeding the control index; the content of defoamer in Comparative Example 3 is too low, and the bubbles generated cannot be quickly eliminated under the impact of pressure on the chain developer, and there are many bubbles; the content of surfactant in Comparative Example 4 is too low, resulting in insufficient wettability of the developer, and it cannot penetrate into the bottom of the graphic during development, and develops on the upper part of the graphic, resulting in a smaller angle; Comparative Example 5 adjusts the type of copper preservative to a commercially available preservative (polyol preservative), which cannot effectively prevent copper corrosion; Comparative Example 6 adjusts the type of defoamer to a commercially available defoamer (silicone system), and bubbles cannot be eliminated during development, and there are many bubbles, and the bubble height is high.

[0061] In summary, the present invention has an important influence on the development cleanliness of the developer, the control of the copper corrosion rate, the steepness of the developed pattern, and the bubble height by adjusting the content and components of the inorganic base, preservative, surfactant, and defoamer.

[0062] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. An alkaline developer composition for solar cell copper interconnection process, characterized in that: The invention comprises the following components by mass percentage: 0.8-1.2% of inorganic alkaline substance, 0.1-0.5% of inorganic buffer, 300-1000ppm of copper preservative, 500-1500ppm of surfactant, 500-1200ppm of defoaming agent, and the rest is pure water.

2. The alkaline developer composition for solar cell copper interconnection process according to claim 1, characterized in that: The copper preservative is selected from one or more of methylbenzotriazole, 2,5-dimercapto-1,3,4-thiadiazole, hydroxybenzothiazole, 3-mercapto-1,2-propylene glycol, 2-thioglycerol, aminotri(methylenephosphonic acid), dithiodiethanol, glycerol, 1,3,5-triazine-2,4,5-trithiol, 2-mercapto-6-hydroxybenzothiazole, and 6-anilino-1,3,5-triazine-2,4-dithiol.

3. The alkaline developer composition for solar cell copper interconnection process according to claim 1, characterized in that: The defoaming agent is selected from one or more of non-silicone polyether higher alcohols and polysiloxanes.

4. The alkaline developer composition for solar cell copper interconnection process according to claim 1, characterized in that: The inorganic alkaline substance is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and ammonia water.

5. The alkaline developer composition for solar cell copper interconnection process according to claim 1, characterized in that: The buffer is selected from one or more of sodium carbonate, sodium bicarbonate, disodium hydrogen phosphate, sodium hydrogen phosphate, sodium oxalate, sodium borate, ammonia water, and sodium borate.

6. The alkaline developer composition for solar cell copper interconnection process according to claim 1, characterized in that: The surfactant is selected from one or more of nonionic fatty acids, polyether-modified heptamethyltrisiloxane, polyether-modified silicone oil, and ether-modified polydimethylsiloxane copolymer.

7. The alkaline developer composition for solar cell copper interconnection process according to claim 1, characterized in that: The conductivity of the pure water is 18.2 megohm-cm.

8. A method for preparing the alkaline developer composition according to any one of claims 1 to 7, characterized in that: The steps include: S1, mixing and dissolving pure water and an inorganic alkaline substance to obtain a mixed solution, and cooling the mixture to room temperature; S2. Adding an inorganic buffer, a copper preservative, a surfactant, and a defoaming agent to the mixed solution at room temperature, mixing and dissolving, and filtering to obtain an alkaline developer composition.

9. The method for preparing the alkaline developer composition according to claim 8, characterized in that: The mixed dissolution conditions are: rotation speed 100-300 rpm, time 0.5-2h.

10. Use of the alkaline developer composition according to any one of claims 1 to 7 in a process for developing a patterned mask layer of a solar cell.